2015
DOI: 10.1016/j.stem.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Induced Emergency Megakaryopoiesis Driven by Hematopoietic Stem Cell-like Megakaryocyte Progenitors

Abstract: Infections are associated with extensive platelet consumption, representing a high risk for health. However, the mechanism coordinating the rapid regeneration of the platelet pool during such stress conditions remains unclear. Here, we report that the phenotypic hematopoietic stem cell (HSC) compartment contains stem-like megakaryocyte-committed progenitors (SL-MkPs), a cell population that shares many features with multipotent HSCs and serves as a lineage-restricted emergency pool for inflammatory insults. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
393
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(421 citation statements)
references
References 41 publications
26
393
1
1
Order By: Relevance
“…Combining our dual detection with other emerging technologies may allow further refinement in the MEP population. Alternate hierarchical models of hematopoiesis have been proposed, wherein a pool of long-term self-renewing stem cells or cells that have the surface phenotype of HSCs and MPPs are already Mk committed 39 or have the ability to commit directly to the Mk lineage. 40 In addition to murine studies cited in the introduction and above, a recently published study suggests that in adult humans, Mk/E activity together with multipotency are restricted to the stem cell compartment with no intermediate bipotent progenitor.…”
Section: Cd41mentioning
confidence: 99%
“…Combining our dual detection with other emerging technologies may allow further refinement in the MEP population. Alternate hierarchical models of hematopoiesis have been proposed, wherein a pool of long-term self-renewing stem cells or cells that have the surface phenotype of HSCs and MPPs are already Mk committed 39 or have the ability to commit directly to the Mk lineage. 40 In addition to murine studies cited in the introduction and above, a recently published study suggests that in adult humans, Mk/E activity together with multipotency are restricted to the stem cell compartment with no intermediate bipotent progenitor.…”
Section: Cd41mentioning
confidence: 99%
“…CD41 has been reported to mark myeloid and megakaryocyte progenitors within the HSC compartment (Haas et al, 2015;Yamamoto et al, 2013), and it's expression increases with age (Gekas and Graf, 2013). Given that myeloid-restricted repopulating cells accumulate in aged mice (Dykstra et al, 2011;Sudo et al, 2000), we hypothesized that by examining CD41 expression we would better understand both the heterogeneity and the myeloid potential within aging HSC compartments.…”
Section: Increased Divisional History Marks Increased Myeloid Potentialmentioning
confidence: 96%
“…However, a recent study 54 demonstrated the presence of a subset of megakaryocyte-committed cells within the immunophenotypically defined HSC compartment that becomes activated upon inflammatory stress to efficiently replenish platelets. During homeostasis, these so called stem-like megakaryocyte-committed progenitors (SL-MkPs) were shown to be mainly quiescent but primed to megakaryocyte commitment because transcripts that encoded several megakaryocyte-associated proteins were actively translated in response to inflammation, resulting in the generation of mature megakaryocytes.…”
Section: Cd42bmentioning
confidence: 99%